Community perspectives of flagship species: can conservation motivators mitigate human-wildlife conflict? - Xu, Wanyun; Xu, Lingxia; Cao, Yuqi; Zheng, Jiaoyang; Wang, Yaling; Cheng, Kun; Lee, Chun-Hung; Dai, Huxuan; Mei, Sonamtso; Zong, Cheng (Frontiers in Ecology and Evolution, 2024)
Public perception of endangered species is crucial for successful management of community-based conservation and sustainability of national parks. Our study evaluated conservation preferences and willingness to donate money for flagship and non-flagship species using a choice experiment with 409 residents living near the Lanstang river source of Sanjiangyuan National Park, China. We found that flagship species such as the Snow leopard (Pristine plateau) and White-lipped deer (Przewalskium albirostris) generated more conservation funds than non-flagship species. However, not all flagship species were accepted. Respondents disliked Tibetan brown bears (Ursus arctos pruinosus) due to direct human-wildlife conflicts such as bodily injury and property damage. Heterogeneity of preference was influenced by household income, religious beliefs, ethnicity, culture, and conservation awareness. Results can be used to establish a local community-participative framework by combining conservation motivations that alleviate human-wildlife conflict.